Fabrication, Characterization, and Adsorption Applications of Low-Cost Hybride Activated Carbons From Peanut Shell-Vinasse Mixtures by One-Step Pyrolysis - Eren, Muhammet Şakir Abdullah; Arslanoğlu, E.; Eren, M.Ş.A.; Arslanoğlu, H.; Çiftçi, H. (Springer Science and Business Media Deutschland GmbH, 2023)
The present work aims to develop an innovative, alternative, fast, and cost-effective one-step pyrolysis method for activated carbon production using peanut shell and vinasse mixture. This facile procedure is based on single-step carbonization treatment at a temperature range of 400–800 °C. Different carbonization time (15–360 min), impregnation ratio (1–3 g/g), impregnation time (3–24 h), and nitrogen flow rate (300 and 600 ml/min) were examined. The chemical and physical properties of the activated carbon examined by SEM-EDX, FT-IR analysis, particle size distribution, iodine number, pHzpc, BET surface area, and surface functional group analysis by Boehm’s titration. The results illustrate that the values of BET surface area, total pore volume, average pore diameter, iodine number, pHzpc, and carbon content of activated carbon were found as 1290.5 m2/g, 0.5667 cm3/g, 21.2 Å, 1258.4 mg/g, 5.7, and 86.89%, respectively. Graphical Abstract: [Figure not available: see fulltext.]. © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH, DE part of Springer Nature.
Keywords: Activated carbon; Adsorption; One-step pyrolysis; Peanut shell; Precursor; Vinasse; Carbonization; Chemical analysis; Cost effectiveness; Impregnation; Iodine; Mixtures; Oilseeds; Particle size; Particle size analysis; Pyrolysis; BET surface area; Carbonisation; Cost effective; Iodine number; Low-costs; One-step pyrolyse; Peanut shells; pH zpc; Precursor; Vinasses; Activated carbon